What drives WTP for energy efficiency when moving? Evidence from a Germany-wide household survey - Martin Kesternich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The political discussion on energy efficiency is focusing more and more on the building sector due to its susceptibility to potential market failures like the negative external pollution effects of CO2 emission. Using a discrete choice approach, this paper aims at deriving factors which increase the willingness to pay (WTP) for energy efficiency in the case of an upcoming move. A multinominal logit model is used to analyse micro data of a survey among more than 200 German households. The estimation results suggest that the WTP is not mainly determined by socioeconomic attributes like household income or formal education, but rather by environmental concerns and energy awareness. Although there is evidence for similarities to research on WTP for green daily consumer goods, the building sector is not clearly perceived as an essential possibility to contribute to climate protection.
Keywords: C25; D12; Q41; 330; Energy efficiency; Multinominal logit model; Residential buildings; Willingness to pay